Analisis Pengaruh Strategi Pemasaran Digital terhadap Keputusan Pembelian Paket Perjalanan Wisata Secara Online pada Objek Wisata Kabupaten Kerinci - Sri Fitriya (Departement of Mathematics Education, 2024)
This research is motivated by the difficulty of tourists getting tour packages that can be accessed online at tourist attractions in Kerinci Regency. These criticisms and suggestions show how enthusiastic tourism service users are in searching for information about a tourist attraction after visiting several tourist attractions in Kerinci Regency, which may be caused by the perpetrator's lack of effort in providing information manually. The aim of this research is to analyze the influence of marketing strategies and tour packages on purchasing decisions. The data analysis used in this research is descriptive and quantitative. The sample in this study was 100 people who had visited one of the tourist attractions in Kerinci Regency. Data collection was carried out using a questionnaire that had been tested for validity and reliability. Data were analyzed using path analysis. The results of statistical testing show that the digital marketing strategy variable has a positive effect on purchasing decisions (hypothesis 1 is accepted), the travel package variable has a positive effect on purchasing decisions (hypothesis 2 is accepted), the digital marketing strategy variable and tour packages together have a positive effect on decisions purchase (hypothesis 3 is accepted)